Concerning Kirk’s problem - Hamid Mottaghi Golshan (Fixed Point Theory and Algorithms for Sciences and Engineering)
Abstract This paper presents a straightforward statement for Khamsi’s theorem without assuming continuity or nondecreasing restrictions on η. Additionally, a new proof provides an affirmative answer to Kirk’s problem, supported by examples. Finally, Ekeland’s variational principle (abbreviated EVP) is developed.